2022
DOI: 10.3390/f13071006
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Turkey Oak, European Beech, and Hornbeam to Gypsy Moth Feeding

Abstract: Pest resistance of trees should be taken into account in future forest strategy planning and predicting risks of defoliation. The gypsy moth (GM) (Lymantria dispar L.) is a serious forest pest with outbreaking population dynamics. To estimate defoliation risk of the most widely distributed tree species in Balkan Peninsula and Europe (Turkey oak Quercus cerris L., European beech Fagus sylvatica L. and hornbeam Carpinus betulus L.), we carried out laboratory feeding trials and investigated their acceptability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Our previous report on SML, which fed on two oak species, showed that amylase was induced on leaves with lower starch content [6]. Moreover, switching from oak to beech leaves containing less nitrogen induced trypsin activity and had no effect on approximate digestibility [135,136]. The importance of protein content and a high P:C ratio for the growth and development of SML is well documented.…”
Section: Temperature-and Diet-induced Plasticity Of Digestive Enzyme ...mentioning
confidence: 96%
“…Our previous report on SML, which fed on two oak species, showed that amylase was induced on leaves with lower starch content [6]. Moreover, switching from oak to beech leaves containing less nitrogen induced trypsin activity and had no effect on approximate digestibility [135,136]. The importance of protein content and a high P:C ratio for the growth and development of SML is well documented.…”
Section: Temperature-and Diet-induced Plasticity Of Digestive Enzyme ...mentioning
confidence: 96%
“…Both of these are key properties of the developmental environment and can affect various traits (e.g. Clissold & Simpson, 2015;Lazarević et al, 2023), but the impact of their interaction on developmental outcome is poorly characterised.…”
Section: Introductionmentioning
confidence: 99%